Synthesis of sp3-rich scaffolds for molecular libraries through complexity-generating cascade reactions. Issue 21 (12th May 2016) - Flagstad, T.; Min, G.; Bonnet, K.; Morgentin, R.; Roche, D.; Clausen, M. H.; Nielsen, T. E.
Abstract : An efficient strategy for the synthesis of complex small molecules from simple building blocks is presented. Abstract : An efficient strategy for the synthesis of complex small molecules from simple building blocks is presented. Key steps of the strategy include tandem Petasis and Diels–Alder reactions, and divergent complexity-generating cyclization cascades from a key dialdehyde intermediate. The methodology is validated through the synthesis of a representative compound set, which has been used in the production of 1617 molecules for the European Lead Factory.